Kinematic and aerodynamic analysis of a bat performing a turning-ascending maneuver. (9th December 2020) - Windes, Peter; Tafti, Danesh K; Müller, Rolf
Abstract: The flapping flight of many bat species is characterized by a high degree of maneuverability and provides fertile ground for biomimetic design. However, there has been little prior work toward understanding bat flight maneuvers, particularly using a coupled kinematic and aerodynamic framework. Here, wing kinematic data of a large insectivorous bat ( Hipposideros armiger ) in straight and turning flight is investigated. Fundamental to turning flight are asymmetries in the wing kinematics and consequently asymmetries in the aerodynamic forces. Forces were calculated from the wing kinematics using aerodynamic numerical simulations. Aspects of the wing kinematics in the turn that were distinguishable from straight flight were an increase in stroke plane deviation angle, nominal increase in flapping amplitude, and a decrease in the horizontal stroke plane angle of the wing inside the turn. While prior work on the mechanics of turning flight in animals has focused on classifying a turn as either banking or yawing, in the present work we show evidence of simultaneous and synergistic banking and yawing mechanisms. During the initiation of the turn, the bank angle was low, and elevated thrust by the outside wing generated a significant yaw rotational moment during both the upstroke and downstroke. Later in the turn, the bank angle increased to approximately 25 degrees tilting the net force vector toward the inside of the turn providing centripetal acceleration thereby turning the bat. Understanding the details of the turning mechanism—combined yaw and bank—provides useful design and control principles for biomimetic flapping MAVs.